Implementation Of Employee Education And Training Based On Duties And Functions In The Secretariat Of The Regional People's Representative Council Of Malang Regency - Ayu Safitri; Tjitjik Rahaju; Indah Prabawati; Firre An Suprapto (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Developing the competency of State Civil Apparatus (ASN) through education and training (diklat) is a strategic need to support bureaucratic reform and improve the quality of government services. The Secretariat of the Malang Regency DPRD, as one of the regional apparatuses, is required to have ASN competent in carrying out its duties and functions, so the implementation of education and training based on tasks and functions is very important. This study aims to analyze and describe the implementation of education and training for employees based on tasks and functions at the Secretariat of the Malang Regency DPRD. The problems found include three things: training participants who often do not match their duties and functions uet o sudden replacements without considering competency suitability, limited information technology facilities that hinder online training, and the absence of specific SOPs that regulate the selection and replacement of participants based on tasks and functions. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation, as well as using data triangulation. The results show that the implementation of training has generally been running but is not fully optimal. Communication is running well through official letters, internal dispositions, and WhatsApp groups. The implementing human resources are competent and the budget is allocated in the Work Plan, but information technology facilities are still limited. The disposition of implementers is positive and supported by TPP incentives, but the sudden replacement of participants, not based on competency, remains unresolved. The bureaucratic structure demonstrates clear fragmentation of tasks, but there are No. specific SOPs that comprehensively regulate the training implementation mechanism.